(untitled) (Olhares, 2025)
São Paulo`s Teatro de Arena, founded in 1953 by José Renato Pécora, with the initial objective of trying out a new and cheaper way of doing theater. Then developed its history to experience a brazilian way to do it and looking for a nationalist theater that was in opposition to the elitist model of the time carried out by the Teatro Brasileiro de Comédia. One of the essential elements for thinking about a Brazilian way of doing theater was to develop, at the same time, a Brazilian way of acting. Actresses and actors from the group gave their testimonies, seeking to present the different ways of doing that developed throughout the rehearsals and shows that guided this search for a “ genuine Brazilian actor”. Teatro de Arena leaves a legacy both in the construction of a Brazilian way of acting and in the elaboration of a dramaturgy that mirrored the national reality.